Optimalisasi Pemberian Pupuk Organik Cair untuk Pertumbuhan Tanaman Kangkung (Ipomea sp.) dengan Sistem Hidroponik - Manek, Maria Putri; Pareira, Magdalena Sunarty; Tuas, Maria Angelina (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to assess the optimization of organic fertilizer in plant growth kale (Ipomea sp.) using a hydroponic system. The research method used is a complete random design of 2 factorial. The first factor is the concentration of POC which consists of 3 levels of treatment, namely K1 = 100 ml POC + 1 L of water. K2 = 200 ml of POC + 2 L of water. K3= 300 ml of POC + 3 L of water. The second factor is the frequency of administration of POC (W) which consists of 3 levels of treatment W1 = every 2 days W2 = every 4 days, W3 = every 6 days. So there are 9 combinations, namely: K1W1, K1W2, K1W3, K2W1, K2W2, K2W3, K3W1, K3W2, K3W3 between treatments with repeated 3 times so that a total of 27 trials. The measured parameters include temperature, plant height, number of leaves and Root Length. The results showed that the interaction occurred at the final temperature, plant height: 21 HST 28 HST, number of leaves: 7 HST, 14 HST ,21 HST and 28 HST and Root Length. The frequency of POC using banana stems with a time of 2 days was able to increase, plant height 21 HST, 28 HST, number of leaves 7 HST,14 HST,21 HST,28 HST, Root Length, while at a frequency of 4 days was able to increase the growth of kale plants in the late afternoon temperature parameters. At a frequency treatment once every 6 days is able to increase the final temperature. Concentration of POC using banana stem with a dose of 100 ml POC +1 L of Water, able to increase plant height 21 HST and 28 HST, the number of leaves 7 HST, 14 HST,21 HST,28 HST, Root Length. This research is expected to contribute to sustainable agricultural practices and the development of efficient hydroponic systems.